ANALISIS KUALITAS PELAYANAN PENDIDIKAN DI SEKOLAH MENENGAH ATAS NEGERI 7 KOTA BENGKULU TAHUN 2025 - Sarwinda Hesti; Budiman Sakti; Henny Aprianty (JURNAL MANAJEMEN MODAL INSANI DAN BISNIS (JMMIB), 2025)
This study aims to analyze in depth the quality of educational services at SMA Negeri 7 Bengkulu City. The focus of this research is on various aspects of educational services such as physical facilities, quality of educators, administrative services, and interaction between teachers and students. The method used is qualitative descriptive with data collection techniques in the form of in-depth interviews, direct observation, and document analysis. The research involved a variety of key informants including school principals, teachers, administrative staff, and students. The results of the study show that despite efforts to improve the quality of services, there are still several weaknesses that need to be corrected immediately, such as the uneven availability of infrastructure facilities and the lack of training to improve teacher competence. These findings make an important contribution to policy-making in improving the quality of education services at the secondary school level. Keywords: quality of service, education, quality, student satisfaction, secondary school